2021
DOI: 10.1016/j.dsx.2021.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study to identify the factors affecting COVID-19 case fatality rates in India

Abstract: Background and aims In India, COVID-19 case fatality rates (CFRs) have consistently been very high in states like Punjab and Maharashtra and very low in Kerala and Assam. To investigate the discrepancy in state-wise CFRs, datasets on various factors related to demography, socio-economy, public health, and healthcare capacity have been collected to study their association with CFR. Methods State-wise COVID-19 data was collected till April 22, 2021. The latest data on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
3
15
1
Order By: Relevance
“…Interestingly, more than half of our study population were younger than 60 years. This finding is in concordance with recent reviews from Bangladesh and India 8,9 ; suggests that the population at risk for COVID-19 mortality may differ from other regions of the world, possibly due to genetic or environmental factors or possibly a shorter life expectancy. Other demographic characteristics, clinical features, co-morbidities and duration of hospital stay were similar to other studies [10][11][12] .…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, more than half of our study population were younger than 60 years. This finding is in concordance with recent reviews from Bangladesh and India 8,9 ; suggests that the population at risk for COVID-19 mortality may differ from other regions of the world, possibly due to genetic or environmental factors or possibly a shorter life expectancy. Other demographic characteristics, clinical features, co-morbidities and duration of hospital stay were similar to other studies [10][11][12] .…”
Section: Discussionsupporting
confidence: 92%
“…Incorporating endurance training into the daily routine of adults affects telomerase activity and telomere length [24] and protects against excessive chromosomal damage [57]. Indeed, many studies have shown a reduction in the number of hospitalisations and the risk of death in COVID-19 patients who had been exercising [58] and were not overweight [59,60]. In addition, aging of the immune system also affects both resistance to infections and the biological age of a person [22,61].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using data from the European Center for Disease Prevention and Control found that the case fatality rate (CFR) was positively associated with the GDP per capita and negatively associated with the number of hospital beds per 1000 people [ 28 ]. Another previous study from India reported that the life expectancy was positively associated with the CFR, whereas the HDI, per capita GDP, health expenditure per capita, number of physicians per 1000 people, and number of hospital beds per 1000 people were negatively associated with the CFR [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These estimations are crucial to the guidance of public health policy [ 27 , 35 ]. A high number of confirmed cases could indicate that extensive testing is taking place, which could then decrease the CFR [ 13 , 34 ]. The CFR is commonly used as a measure of the disease severity and efficiency of treatment.…”
Section: Discussionmentioning
confidence: 99%